THE ROLE OF CUSTOMER SATISFACTION IN MEDIATING THE EFFECT OF PERCEIVED VALUE ON GOJEK CUSTOMER LOYALTY IN MEDAN CITY - Siregar, Arifah Rakatasya; Fadillah, Risydah; Lubis, Rahmi (International Journal of Cultural and Social Science, 2026)
The rapid expansion of app-based transportation services in Indonesia has intensified competition and increased customer switching, making loyalty a critical challenge for market leaders such as Gojek. This study investigates how perceived value influences customer loyalty and examines the mediating role of customer satisfaction among Gojek users in Medan City. A quantitative explanatory design was employed using an online survey administered from 6–20 November 2025. Data were collected from 375 respondents selected through purposive sampling and analyzed using PLS-SEM (SmartPLS). The findings show that perceived value positively and significantly affects customer loyalty (? = 0.350; p < 0.001) and strongly predicts customer satisfaction (? = 0.691; p < 0.001). Customer satisfaction also has a significant positive effect on loyalty (? = 0.553; p < 0.001). Mediation analysis confirms that customer satisfaction significantly mediates the relationship between perceived value and loyalty (?_indirect = 0.382; p < 0.001), indicating that the value–loyalty link is predominantly realized through satisfaction. The study reinforces the value–satisfaction–loyalty chain in digital service contexts and highlights that strengthening multidimensional perceived value—especially experiential and emotional components—can enhance satisfaction and sustain customer loyalty in highly competitive online transportation markets.